Analisis Pertimbangan Hakim dalam Penjatuhan Pidana terhadap Residivis Tindak Pidana Pembunuhan: Studi Putusan Nomor 7/PID.B/2023/PN KLA - Sukowati Sukowati; Fristia Berdia Tamza; Eko Raharjo; Firganefi Firganefi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Criminal law aims to maintain order and justice in society through the criminalization of criminals. One form of serious crime is the crime of murder, which is expressly regulated in the Criminal Code. This crime is a serious concern given the high impact it causes, especially when it is committed repeatedly or by a rwsidivis. The recidivism case of murder contained in Decision Number 7/Pid.B/2023/Pn Kla shows the complexity in the criminal sentencing process. The defendant had previously been convicted in a murder case, but returned to commit a similar crime shortly after his sentence. The prosecutor demanded a sentence of 15 years in prison, and the judge ruled in accordance with article 338 of the Criminal Code without applying the criminal burden as stipulated in the provisions on recidivism. This raises questions related to the basis of judge's consideration and its relevance to the purpose of criminal law, especially in providing a deterrent and justice effect for the community. The problem in this study is what is the basis for the judge's consideration in imposing a criminal sentence on a recidivist for the crime of murder, and whether the verdict has fulfilled the purpose of sentencing a recidivist perpetrator of the crime of murder.